The H3K27me3 Demethylase RELATIVE OF EARLY FLOWERING6 Suppresses Seed Dormancy by Inducing Abscisic Acid Catabolism. Issue 4 (9th October 2020) - Chen, Huhui; Tong, Jianhua; Fu, Wei; Liang, Zhenwei; Ruan, Jiuxiao; Yu, Yaoguang; Song, Xin; Yuan, Liangbing; Xiao, Langtao; Liu, Jun; Cui, Yuhai; Huang, Shangzhi; et al.
Abstract : H3K27me3 demethylase REF6 suppresses seed dormancy and promotes seed germination by enhancing the catabolism of the plant hormone Abscisic acid. Abstract: Seed dormancy is an adaptive trait that is crucial to plant survival. Abscisic acid (ABA) is the primary phytohormone that induces seed dormancy. However, little is known about how the level of ABA in seeds is determined. Here we show that the Arabidopsis ( Arabidopsis thaliana ) H3K27me3 demethylase RELATIVE OF EARLY FLOWERING6 (REF6) suppresses seed dormancy by inducing ABA catabolism in seeds. Seeds of the ref6 loss-of-function mutants displayed enhanced dormancy that was associated with increased endogenous ABA content. We further show that the transcripts of two genes key to ABA catabolism, CYP707A1 and CYP707A3, but not genes involved in ABA biosynthesis, were significantly reduced in ref6 mutants during seed development and germination. In developing siliques, REF6 bound directly to CYP707A1 and CYP707A3, and was responsible for reducing their H3K27me3 levels. Genetic analysis demonstrated that the enhanced seed dormancy and ABA concentration in ref6 depended mainly on the reduced expression of CYP707A1 and CYP707A3 . Conversely, overexpression of CYP707A1 could offset the enhanced seed dormancy of ref6 . Taken together, our results revealed an epigenetic regulation mechanism that is involved in the regulation of ABA content in seeds.